Short term load forecasting algorithm in transmission system - 373768 Ibrahim Salem Ali Salem; Ahmad Safawi Mokhtar, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2008